The impact of “internet of things”: advancing patient monitoring and health outcomes to enhance healthcare quality: a systematic review - Kumari, Ritu; Kalyani, B.; Dabhi, Pratibha; Malhotra, Kashish; Mundotiya, Meenakshi; Khatodiya, Rajveer S.; Suhashini; Umar, Mohammed (International Journal of Clinical Trials, 2025)
The internet of things (IoT) has emerged as a transformative force in healthcare, reshaping patient monitoring, data collection, and clinical decision-making. As the global healthcare landscape becomes increasingly digitized, understanding the contributions of IoT to quality enhancement is critical. This systematic review explores the current evidence on the impact of IoT on patient monitoring and health outcomes, focusing on its role in improving healthcare quality. A comprehensive search of PubMed, Scopus, IEEE Xplore, and Google Scholar databases was conducted for studies published between January 2015 and May 2025. Keywords included “IoT in healthcare,” “patient monitoring,” “health outcomes,” and “quality improvement.” Studies were included if they focused on IoT applications in healthcare settings with measured outcomes related to patient care or quality. Preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines were followed. A total of 58 studies were included. The majority demonstrated significant improvement in early detection of clinical deterioration, chronic disease management, remote patient monitoring, and reduction in hospital readmissions. IoT was found to enhance real-time decision-making, lower operational costs, and improve patient satisfaction and safety metrics. IoT plays a pivotal role in advancing healthcare delivery by enhancing monitoring capabilities and health outcomes. However, ethical challenges, cybersecurity concerns, and interoperability barriers remain. Strategic investments and regulatory frameworks are essential for sustainable IoT integration.